Analysis of The Influence of Negative E-Word of Mouth on Brand Disloyalty and Distrust of Digital Payment Application Users - Firdaus Yuni Dharta; Haniwijaya Pahlawansah; Amin Budiastuti; Novi Rahayu; Mutiasari (SEULANGA SYSTEM PUBLISHER, 2023)
This study examines the possibility that brand mistrust mediates the indirect impact of unfavorable e-WOM on brand disloyalty among users of financial applications. Users of financial applications make up the research's sample population. With a total of 100 respondents, the researchers sampled using the non-probability sampling approach. Quantitative data is the type of information that researchers employ. In this study, questionnaires were used to gather data. Path analysis is the data analysis technique applied by the researchers in this study. According to research findings, bad E-WOM has an impact on consumers' mistrust of brands. Negative E-WOM has an impact on brand disloyalty. Brand disloyalty is not partially influenced by brand mistrust. Negative E-WOM and brand mistrust both have an impact on brand disloyalty simultaneously. Negative E-WOM does not have an indirect impact on brand disloyalty, which is mediated by brand distrust.